2021
DOI: 10.1016/j.mayocp.2021.03.033
|View full text |Cite
|
Sign up to set email alerts
|

My Treatment Approach to Clostridioides difficile Infection

Abstract: Clostridioides difficile infection is the most common cause of infectious diarrhea in hospitals with an increasing incidence in the community. Clinical presentation of C difficile infection ranges from diarrhea manageable in the outpatient setting to fulminant infection requiring intensive care admission. There have been significant advances in the management of primary and recurrent C difficile infection including diagnostics, newer antibiotics, antibody treatments, and microbiome restoration therapies. Becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…FMT has been successfully used in the treatment of Clostridium difficile infection (CDI) and IBD [ 65 , 66 ]. An interesting study included Blastocystis -positive (ST1 and ST3) donor samples for FMT treatment of recurrent CDI, and demonstrated that the presence of Blastocystis ST1 and ST3 from donors did not cause any adverse gastrointestinal symptoms [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…FMT has been successfully used in the treatment of Clostridium difficile infection (CDI) and IBD [ 65 , 66 ]. An interesting study included Blastocystis -positive (ST1 and ST3) donor samples for FMT treatment of recurrent CDI, and demonstrated that the presence of Blastocystis ST1 and ST3 from donors did not cause any adverse gastrointestinal symptoms [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clostridioides difficile is the most common causative agent of infectious diarrhea in hospitalized patients; although, community-acquired C. difficile infection (CDI) has also become epidemiologically and clinically relevant during the last decade [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Gram-positive anaerobic bacterium Clostridioides difficile is among the main pathogens responsible for nosocomial diarrhea, causing significant morbidity, mortality, prolonged hospital stay and high healthcare costs worldwide [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. A relevant issue during CDI is its high rate of recurrences (rCDI).…”
Section: Introductionmentioning
confidence: 99%